Assessment of probiotic properties of Lactobacillus plantarum ZLP001 isolated from gastrointestinal tract of weaning pigs - Jing Wang, Haifeng Ji; Dongyan Zhang, Hui Liu, Sixin Wang, Dacong Shan; Yamin Wang (African Journal of Pig Farming, 2017)
The probiotic potential of Lactobacillus plantarum ZLP001, isolated from the gastrointestinal tract of a healthy weaning piglet, was assessed as a probiotic in vitro and in vivo. The survival rate of L. plantarum ZLP001 when cultured in simulated gastric fluid with pH 2.0 and 3.0 and subsequent in intestinal fluid pH 8.0 was determined and the results show that this strain had resistance to pH 3.0 simulated gastric fluid and subsequent pH 8.0 intestinal fluid. Bile salt resistance of this strain was examined in deMan, Rogosa and Sharpe (MRS) broth containing oxgall concentration from 0.1% to 0.5%. The strain showed 85.3 and 61.4% bile tolerance under 0.1 and 0.3% bile salt, respectively, and was inhibited in 0.5% bile salt (9.4%). The sizes of the inhibitory zone of this strain against Staphylococcus aureus, Escherichia coli, and Salmonella enterica were also determined. The result shows that this strain had high antimicrobial activity against selected pathogens. The probiotic strain was administered through the feed to 35-day old weaned piglets to estimate the effect of L. plantarum ZLP001 on the growth performance. 80 piglets were selected and divided into five groups comprising of negative control without any supplementation, three treatments of different L. plantarum ZLP001 levels (5.9×107 , 3.5×108 , and 1.8×109 CFU/g of diet), and positive control with antibiotic treatment (chlorotetracycline, 0.3% of diet). The results of feeding trial showed that L. plantarum ZLP001 supplementation enhanced feed conversation rates in piglets compared with control. The present study implies that the strain L. plantarum ZLP001 was considered to be a potential probiotic for weaned piglets.